Foreword for isotopic generalizations of quantum theories - Davies J. Dunning (Ratio Mathematica, 2024)
Here it is attempted to give a brief introduction to the work of Ruggero San- tilli via a slightly more detailed discussion of two areas in which he has made major contributions. The motivation for his work is also discussed through- out and an attempt is made also to highlight some of the problems which have inspired him over the years. The two examples taken are, firstly, a fas- cination with the early work of Rutherford in viewing a neutron, which was undiscovered at the time, as a proton and an electron. This model was dis- carded because it wasn’t allowed by conventional quantum mechanics. The second was a deep interest in the paradox introduced into physics by the ap- pearance of the now famous article by Einstein, Podolsky and Rosen in 1935. Both these contributed to Santilli’s realization that, for further progress to be made in physics, a new approach had to be adopted which would involve the use of as yet unused, or unknown, mathematical methods. Over the years, a huge body of new mathematics has emerged through the efforts of Santilli, helped to some extent by various other workers, but the main body has been due to him. This relatively short foreword has as its aim to promote this lifetime’s work of Santilli and hopefully encourage others to be motivated to study it with truly open minds and, where necessary, carry out actual ex- periments to test independently some of the predictions made – especially the one relating to a possible method for the safe, rapid disposal of nuclear waste.